2017
DOI: 10.1002/bip.23014
|View full text |Cite
|
Sign up to set email alerts
|

Log D versus HPLC derived hydrophobicity: The development of predictive tools to aid in the rational design of bioactive peptoids

Abstract: Hydrophobicity has proven to be an extremely useful parameter in small molecule drug discovery programmes given that it can be used as a predictive tool to enable rational design. For larger molecules, including peptoids, where folding is possible, the situation is more complicated and the average hydrophobicity (as determined by RP‐HPLC retention time) may not always provide an effective predictive tool for rational design. Herein, we report the first ever application of partitioning experiments to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…To investigate the effect of sPEGs attached at the termini or inserted at various positions within the sequence, these moieties were introduced via commercially available amino acids containing varying repeats (n times) of oxyethylene units (i.e., sPEGn; Figure 1). highly cationic peptides and peptidomimetics [17,36,[41][42][43][44]. Recently, within a large set of peptidomimetics, resembling those in the present study, we identified a correlation between hydrophobicity (expressed as percent acetonitrile at peak elution in analytical RP-HPLC) and both antibacterial activity and hemolytic properties [17].…”
Section: Selection and Synthesis Of Peptidomimeticssupporting
confidence: 66%
See 1 more Smart Citation
“…To investigate the effect of sPEGs attached at the termini or inserted at various positions within the sequence, these moieties were introduced via commercially available amino acids containing varying repeats (n times) of oxyethylene units (i.e., sPEGn; Figure 1). highly cationic peptides and peptidomimetics [17,36,[41][42][43][44]. Recently, within a large set of peptidomimetics, resembling those in the present study, we identified a correlation between hydrophobicity (expressed as percent acetonitrile at peak elution in analytical RP-HPLC) and both antibacterial activity and hemolytic properties [17].…”
Section: Selection and Synthesis Of Peptidomimeticssupporting
confidence: 66%
“…While partition coefficients, e.g., log D values, are typically utilized in the estimation of the hydrophobicity of small molecules, the relative retention in reverse-phase HPLC (RP-HPLC) represents a more appropriate measure of hydrophobicity for very polar and highly cationic peptides and peptidomimetics [17,36,[41][42][43][44]. Recently, within a large set of peptidomimetics, resembling those in the present study, we identified a correlation between hydrophobicity (expressed as percent acetonitrile at peak elution in analytical RP-HPLC) and both antibacterial activity and hemolytic properties [17].…”
Section: Introductionmentioning
confidence: 99%
“…All compounds 1 – 6 formed supramolecular hydrogels as confirmed by oscillatory rheology (see Supporting Information , Section S8). The minimum gelling concentration (mgc) was inversely proportional to the HPLC retention time, which is an experimental measure of hydrophobicity, 37 as shown in Table 1 . However, not all hydrogels were stable over time ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, from the rheological analysis, we inferred that heterochirality promoted hydrogelation, since in the case of Leu-Phe, it reduced gelation time, while in the case of Phe-Leu, it yielded a gel in contrast to the non-gelling L-isomer. The reasons behind this phenomenon could lie in the hydrophobicity increase, as supported by HPLC retention times (Rt), 33 which were higher for heterochiral than homochiral isomers (Table 1). It was recently demonstrated on hydrophobic tripeptides that heterochirality oriented the side chains on the same side of the peptide backbone, contrarily to the L-isomers.…”
Section: Resultsmentioning
confidence: 99%